Ar ARTIKEL REVIEW, KEUNGGULAN PROTEIN IKAN DIBANDINGKAN PROTEIN NON IKAN LAINNYA - Junianto, Junianto; Syauqibik, Achmad (Jurnal Perikanan Unram, 2025)
Protein is an essential macronutrient component in fulfilling human nutritional needs. Fish asa source of animal protein has unique nutritional characteristics that make it a potential high-quality food source. This study aims to review the advantages of fish protein compared to non-fish protein through a systematic review method. Data collection used the Google Chromesearch engine with keywords fish protein, advantages of fish protein, and non-fish protein on30 literature published from 2014-2025. Furthermore, the data were analyzed descriptivelycomparative. The review results show that fish protein content (19.9-58.8%) is higher than non-fish protein (1.59-19.76%), with tilapia and snakehead fish leading (58.8% and 53.17%). Theamino acid profile of fish is also superior, indicated by the presence of tryptophan in snakeheadfish (0.13%) and striped snakehead (0.14%) which is not detected in non-fish sources. Seahorseshows significant advantages in arginine content (3.55%), valine (3.38%), leucine (4.22%), andlysine (6.8%). It can be concluded that fish protein is superior to non-fish protein, both in termsof quantity and quality, making it an excellent source of animal protein for fulfilling humannutritional needs.Key words: Amino Acid, Animal Protein, Fish, Nutritional Composition, Protein